2010
DOI: 10.1155/2010/340849
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors of Energy Metabolism Associated with Myopathies

Abstract: Inherited neuromuscular disorders affect approximately one in 3,500 children. Structural muscular defects are most common; however functional impairment of skeletal and cardiac muscle in both children and adults may be caused by inborn errors of energy metabolism as well. Patients suffering from metabolic myopathies due to compromised energy metabolism may present with exercise intolerance, muscle pain, reversible or progressive muscle weakness, and myoglobinuria. In this review, the physiology of energy metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 161 publications
0
50
0
19
Order By: Relevance
“…During catabolic circumstances such as prolonged fasting, stress, illness, and surgery, metabolic derangement can occur, resulting in hypoglycemia, myopathies (including cardiomyopathy), metabolic acidosis, and rhabdomyolysis (Leslie et al 1993;Redshaw and Stewart 2014). Current treatment consists of avoiding catabolism with regular feedings and in some patients a restriction of long chain fatty acids, supplementation of medium chain triglycerides, and frequent carbohydrate intake to prevent activation of fatty acid metabolism (Arnold et al 2009;Das et al 2010). The metabolic derangement during surgery depends, amongst others, on disease severity which is related to residual enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…During catabolic circumstances such as prolonged fasting, stress, illness, and surgery, metabolic derangement can occur, resulting in hypoglycemia, myopathies (including cardiomyopathy), metabolic acidosis, and rhabdomyolysis (Leslie et al 1993;Redshaw and Stewart 2014). Current treatment consists of avoiding catabolism with regular feedings and in some patients a restriction of long chain fatty acids, supplementation of medium chain triglycerides, and frequent carbohydrate intake to prevent activation of fatty acid metabolism (Arnold et al 2009;Das et al 2010). The metabolic derangement during surgery depends, amongst others, on disease severity which is related to residual enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…As SM energy demand varies by several orders of magnitude from resting to exercise conditions, energy metabolism is tightly regulated in order to meet the widely varying energy requirements (Das et al 2010). For over two decades, clinical and experimental studies have shown that deranged SM energy metabolism underlies weakness and early fatigability in metabolic myopathies (Radda 1986;Wortmann 1991) and muscular dystrophies (Radda 1986;Das et al 2010). Further, aging is associated with altered SM energy metabolism (Russ and Lanza 2011) and longitudinal studies have shown that energy availability declines Skeletal muscle catalase activity and protein carbonylation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were designed to test for the first time whether or not abnormalities in energy metabolism, associated with weakness in other myopathies (Radda 1986;Wortmann 1991;Das et al 2010) and muscular dystrophies (Radda 1986;Younkin et al 1987;Barnes et al 1997), are present in vivo at rest in aged IL10 tm/tm mice. They were not designed to determine whether or not energetic abnormalities cause the muscle weakness that was previously established in this model (Walston et al 2008).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three primary metabolic myopathies are mitochondrial myopathies, lipid metabolism myopathies, and glycogen metabolism myopathies [14]. The mitochondrial myopathies may present with multi-systemic features [15].…”
Section: Clinical Presentation Of the Metabolic Myopathiesmentioning
confidence: 99%